Psychometric properties of the Epworth Sleepiness Scale in Brazilian medical students - Renato Canevari Dutra da Silva; Anderson Garcez; Adriana Vieira Macedo Brugnoli; Marcos Pascoal Pattussi; Maria Teresa Anselmo Olinto (Arquivos de Neuro-Psiquiatria)
Background Excessive daytime sleepiness (EDS) refers to the propensity to become drowsy or fall asleep when the intention and expectation would be to stay awake, and the Epworth Sleepiness Scale (ESS) is an easy-to-apply instrument that can be used to assess the presence of EDS.